Controlling the Surface Reactivity of Hybrid Ti3CN MXene via In‐situ Electrocatalysis. Issue 21 (6th October 2022) - Uwadiunor, Ekenedilichukwu; Johnson, Denis; Hansen, Kyle; Djire, Abdoulaye
Abstract: Two‐dimensional (2D) carbide and nitride MXenes possess properties that are desirable for a broad range of electrocatalytic applications including the hydrogen evolution reaction (HER). These properties include high surface area, hydrophilicity, heterogeneity of redox‐active transition metals, and tunable surface functionalities allowing for low HER overpotentials. In this paper, we report on the cathodic etching and −O/−OH functionalization of hybrid Ti3 CN upon the application of an external potential for improved HER performance and show that the active sites for HER on this MXene catalyst are located primarily on the −O− and −OH functional groups. The overpotential for the hybrid Ti3 CN improves by 350 mV upon in‐situ −O/−OH functionalization and etching, reaching −0.46 V vs. RHE at a current density of 10 mA cm −2, much lower than those reported for the benchmark Ti3 C2 carbide MXene. These results provide a path forward to tuning the electrocatalytic activity of MXenes and related electrocatalysts for water splitting. Abstract : Surfaces : Functional groups on the surface of hybrid Ti3 CN MXenes are selectively tuned by in‐situ electrocatalysis. The fluorine termination groups are replaced by oxide and hydroxyl groups leading to more favorable HER performance.